Efficacy of e-FAST in the Detection of Free Intraperitoneal Fluid Following Blunt Abdominal Trauma: A Cross-Sectional Study from Shahroud, Iran - Karimi Goudarzi, Gelareh; Amiri Largani, Hossein; Abbaszadeh, Maryam; Yekesadat, Seyed Meysam; Sohrabi, Mohammad Bagher; Abbasi, Ali (Shahroud Journal of Medical Sciences, 2026)
Background: Blunt abdominal trauma is among the most critical injuries in emergency medicine, often requiring rapid diagnosis to prevent morbidity and mortality. Although computed tomography (CT) scan with intravenous (IV) contrast remains the gold standard for detecting intraperitoneal free fluid, limitations such as cost and availability necessitate alternative tools like the extended Focused Assessment with Sonography for Trauma (e-FAST). This study aimed to determine the diagnostic accuracy of e-FAST ultrasonography in identifying free intraperitoneal fluid among trauma patients.Methods: In this cross-sectional analytical study, 110 patients with blunt abdominal trauma admitted to Imam Hossein Hospital in Shahroud during 2019 were evaluated. After clinical examination, all patients underwent e-FAST ultrasonography followed by abdominal CT with IV contrast scan as the reference standard. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of e-FAST were calculated and compared with CT findings.Results: Of the 110 patients, 82 (74.5%) were male. The mean age was 39.15 ± 17.52 years, with the highest prevalence in the 36–50 age group. e-FAST findings showed a sensitivity of 76%, specificity of 82%, PPV of 74.5%, NPV of 79%, and overall diagnostic accuracy of 91% in detecting free intraperitoneal fluid compared to CT scan. The area under the ROC curve was 0.855, indicating excellent diagnostic performance.Conclusion: The e-FAST ultrasonography demonstrates high accuracy and acceptable sensitivity and specificity for detecting free fluid in patients with blunt abdominal trauma. Given its accessibility and low cost, e-FAST can be considered a reliable initial diagnostic tool, although CT scan remains necessary in equivocal or high-risk cases.